Quantification of the credit risk of banks in Bosnia and Herzegovina regarding the individual members of the EU - Alihodžić, Almir (Kwantyfikacja ryzyka kredytowego banków Bośni i Hercegowiny odnośnie do indywidualnych członków UE, 2017)
Credit risk is the most important risk among all other risks in the banking business, because almost over 80% of bank balance sheets relate to this segment of banking risk management. One of the biggest problems of commercial banks in Bosnia and Herzegovina are non-performing loans whose share in total loans has increased significantly since the onset of the global financial crisis. The main objective of the research is to determine which of the macroeconomic variables have the strongest impact on the increase of return on average equity and whether it is possible to reduce the credit risk of banks with adequate legislation as the main factor in the slowdown in credit expansion. The main goal will be to divide the impact of an independent variable, i.e. the share of liquid assets in total assets and whether its increase indirectly affects the return on equity and indirectly, the credit risk. The quantitative model used in this study will be the Merton model. Testing will be conducted through multiple regression analysis for the period 2008-2016 with the help of the software package STATA
Nauki o Finansach = Financial Sciences, 2017, Nr 4 (33), s. 9-21
Keywords: return on average equity; regression analysis; the stability of the financial system; credit risk; rentowność średniego kapitału własnego; analiza regresywna; stabilność systemu finansowego; ryzyko kredytowe